Analysis of Factors Influencing Outcomes in Preterm Infants With Necrotizing Enterocolitis - Han, JinBao; Liu, Gang; Yu, MengNan; Li, Guang; Cao, JianYing; Duan, Lian; Huang, LiuMing (Frontiers in Pediatrics, 2022)
Abstract Background: To explore the surgical outcomes between patients with perforated and non-perforated neonatal necrotizing enterocolitis (NEC) and identify indications for surgical intervention. Methods: The surgical outcomes of 271 children with NEC admitted to the Seventh Medical Center of Chinese PLA General Hospital between August 2009 and August 2020 were retrospectively analyzed. The patients were divided into the non-perforated and perforated groups. The preoperative factors, including gestational age, birth weight, intrauterine infection, cholestasis, platelet change, white blood cell count, and C-reactive protein level were compared between the two groups, along with postoperative factors including infection status, complications, enteral and parenteral nutrition time, ICU time, ventilator use time, and intestinal necrosis length. Bell staging was performed for the two groups and the mortality of different Bell stages was explored. The risk of death and predisposing factors of patients with NEC were analyzed. Results: In total, 271 children undergoing surgery were included in this study. A total of 188 children were observed without perforation, including 57 deaths (30.3%), and 83 children with perforation, including 24 deaths (28.9%). Preoperative cholestasis and time from NEC diagnosis to surgery were significantly different between the two groups (P < 0.05). Postoperative factors, including parenteral nutrition time (32 [3–94] days vs. 23 [1–53] days), enteral nutrition time (27 [0–86] days vs. 18 [0–81] days), NICU time (44 [5–125] days vs. 29 [1–92] days), and length of intestinal necrosis (15 [0–92] cm vs. 10 [2–70] cm), were significant. The mortality rate of patients with Bell stage IIIA was higher than that of patients with Bell stage IIIB. A total of 81 patients had 30-day postoperative mortality (57 non-perforated cases). Multivariate Cox regression analysis showed that non-perforation was a poor prognostic factor for survival outcome (hazard ratio 2.288, 95% confidence interval [1.329–3.940], P = 0.003). Conclusions: Preterm infants in the non-perforated group had more serious complications and had a longer recovery time after surgery. Bell staging is not accurate in diagnosing severe NEC that needs surgical intervention.